(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyses political discourse by focusing on the speeches of Margaret Thatcher and Theresa May, the prime ministers of the United Kingdom. The goal is to study how the situation or culture during their tenure influenced their speech. Additionally, the examples demonstrate how the use of modal verbs and sentence structure in their speeches affected the ministers’ political personas and management styles.